2019
DOI: 10.1093/mnras/stz3090
|View full text |Cite
|
Sign up to set email alerts
|

Spiral arms in the protoplanetary disc HD100453 detected with ALMA: evidence for binary–disc interaction and a vertical temperature gradient

Abstract: Scattered light high-resolution imaging of the proto-planetary disc orbiting HD100453 shows two symmetric spiral arms, possibly launched by an external stellar companion. In this paper we present new, sensitive high-resolution (∼30 mas) Band 7 ALMA observations of this source. This is the first source where we find counterparts in the sub-mm continuum to both scattered light spirals. The CO J=3-2 emission line also shows two spiral arms; in this case they can be traced over a more extended radial range, indica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
96
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(114 citation statements)
references
References 94 publications
12
96
1
Order By: Relevance
“…So far no clear spiral structures have been found in the dust continuum (or optically thin lines) of CQ Tau that could be used to further distinguish possible launching scenarios, but these could be made accessible with higher spectral and spatial resolution data. Spiral arms have been observed with ALMA in the continuum of several discs, including for example Elias 2-27 (Pérez et al 2016), IM Lup and WaOph 6 (Huang et al 2018), G17.64+0.16 (Maud et al 2019), MWC 758 (Boehler et al 2018;Dong et al 2018), and HD100453 (Rosotti et al 2020b). For the latter, counterparts to the observed NIR spirals (Wagner et al 2015;Benisty et al 2017) were not only found in the dust continuum but also the CO emission, enabling the authors to study the thermal structure of the disc and link the spirals to a known binary companion.…”
Section: Discussionmentioning
confidence: 99%
“…So far no clear spiral structures have been found in the dust continuum (or optically thin lines) of CQ Tau that could be used to further distinguish possible launching scenarios, but these could be made accessible with higher spectral and spatial resolution data. Spiral arms have been observed with ALMA in the continuum of several discs, including for example Elias 2-27 (Pérez et al 2016), IM Lup and WaOph 6 (Huang et al 2018), G17.64+0.16 (Maud et al 2019), MWC 758 (Boehler et al 2018;Dong et al 2018), and HD100453 (Rosotti et al 2020b). For the latter, counterparts to the observed NIR spirals (Wagner et al 2015;Benisty et al 2017) were not only found in the dust continuum but also the CO emission, enabling the authors to study the thermal structure of the disc and link the spirals to a known binary companion.…”
Section: Discussionmentioning
confidence: 99%
“…However, theoretical models have shown that in addition to binary-disk interactions, several different processes can also drive the generation of spirals in disks, such as a low-mass companion on an orbit inside or outside of the disk (e.g., Dong et al 2015a), gravitational instability (e.g., Dong et al 2015b;Dipierro et al 2015;Nelson & Marzari 2016;Meru et al 2017), or a combination of both (e.g., Pohl et al 2015), as well as temperature fluctuations as a result of shadowing by a warped or misaligned inner disk (e.g., Montesinos et al 2016). In order to discern between the companion and gravitational instability scenario, observations at comparably high resolution of the dust continuum, probing the midplane of the disk, are required (e.g., Rosotti et al 2020). However, we regard the last scenario as rather unlikely because in this case, the spiral arms would be expected to diverge from a location close to where the scatteredlight shadows are located.…”
Section: Spiral Structures As Imprints Of Binary-disk Interactionmentioning
confidence: 99%
“…The Atacama Large Millimeter/Submillimeter Array (ALMA) is rapidly revolutionizing the field of proto-planetary discs thanks to transformational improvements in sensitivity and spatial resolution compared to the previous generation of sub-mm interferometers. One of the most important discoveries of the last few years is the realisation that most proto-planetary discs are not smooth, but have a wide variety of sub-structures such as gaps (ALMA Partnership et al 2015;Andrews et al 2016), spirals (Pérez et al 2016;Boehler et al 2018;Rosotti et al 2020a) and crescents (Casassus et al 2013;van der Marel et al 2013;Cazzoletti et al 2018), at least for what concerns the dust emission.…”
Section: Introductionmentioning
confidence: 99%